Loss-of-function mutations in cause a new form of inherited thrombocytopenia. - Marconi, Caterina; Di Buduo, Christian A; LeVine, Kellie; Barozzi, Serena; Faleschini, Michela; Bozzi, Valeria; Palombo, Flavia; McKinstry, Spencer; Lassandro, Giuseppe; Giordano, Paola; Noris, Patrizia; Balduini, Carlo L; et al. (Blood, 2019)
Inherited thrombocytopenias (ITs) are a heterogeneous group of disorders characterized by low platelet count that may result in bleeding tendency. Despite progress being made in defining the genetic causes of ITs, nearly 50% of patients with familial thrombocytopenia are affected with forms of unknown origin. Here, through exome sequencing of 2 siblings with autosomal-recessive thrombocytopenia, we identified biallelic loss-of-function variants in This gene encodes for a receptor-like PTP, PTPRJ (or CD148), which is expressed abundantly in platelets and megakaryocytes. Consistent with the predicted effects of the variants, both probands have an almost complete loss of PTPRJ at the messenger RNA and protein levels. To investigate the pathogenic role of PTPRJ deficiency in hematopoiesis in vivo, we carried out CRISPR/Cas9-mediated ablation of (the ortholog of human ) in zebrafish, which induced a significantly decreased number of CD41 thrombocytes in vivo. Moreover, megakaryocytes of our patients showed impaired maturation and profound defects in SDF1-driven migration and formation of proplatelets in vitro. Silencing of in a human megakaryocytic cell line reproduced the functional defects observed in patients' megakaryocytes. The disorder caused by mutations presented as a nonsyndromic thrombocytopenia characterized by spontaneous bleeding, small-sized platelets, and impaired platelet responses to the GPVI agonists collagen and convulxin. These platelet functional defects could be attributed to reduced activation of Src family kinases. Taken together, our data identify a new form of IT and highlight a hitherto unknown fundamental role for PTPRJ in platelet biogenesis.

MYH9-Related Thrombocytopenia: Four Novel Variants Affecting the Tail Domain of the Non-Muscle Myosin Heavy Chain IIA Associated with a Mild Clinical Evolution of the Disorder. - Zaninetti, Carlo; De Rocco, Daniela; Giangregorio, Tania; Bozzi, Valeria; Demeter, Judit; Leoni, Pietro; Noris, Patrizia; Ryhänen, Samppa; Barozzi, Serena; Pecci, Alessandro; Savoia, Anna (Hamostaseologie, 2019)
-related disease (-RD) is an autosomal-dominant thrombocytopenia caused by mutations in the gene for non-muscle myosin heavy chain IIA (NMMHC-IIA). Patients present congenital macrothrombocytopenia and inclusions of NMMHC-IIA in leukocytes, and have a variable risk of developing kidney damage, sensorineural deafness, presenile cataracts and/or liver enzymes abnormalities. The spectrum of mutations found in -RD patients is limited and the incidence and severity of the non-congenital features are predicted by the causative variant. In particular, different alterations of the C-terminal tail domain of NMMHC-IIA associate with remarkably different disease evolution. We report four novel mutations affecting the tail domain of NMMHC-IIA and responsible for -RD in four families. Two variants cause amino acid substitutions in the coiled-coil region of NMMHC-IIA, while the other two are a splicing variant and a single nucleotide deletion both resulting in frameshift alterations of the short non-helical tailpiece. Characterization of phenotypes of affected individuals shows that all of these novel variants are associated with a mild clinical evolution of the disease.

Clinical and pathogenetic features of ETV6 related thrombocytopenia with predisposition to acute lymphoblastic leukemia. - Melazzini, Federica; Palombo, Flavia; Balduini, Alessandra; De Rocco, Daniela; Marconi, Caterina; Noris, Patrizia; Gnan, Chiara; Pippucci, Tommaso; Bozzi, Valeria; Faleschini, Michela; Barozzi, Serena; Doubek, Michael; et al. (Haematologica, 2016)
ETV6-related thrombocytopenia (ETV6-RT) is an autosomal dominant thrombocytopenia that has been recently identified in a few families and has been suspected to predispose to hematological malignancies. To gain further information on this disorder, we searched for ETV6 mutations in the 130 families with inherited thrombocytopenia of unknown origin from our cohort of 274 consecutive pedigrees with familial thrombocytopenia. We identified 20 ETV6-RT patients from 7 pedigrees. They have 5 different ETV6 variants, including three novel mutations affecting the highly conserved E26 transformation-specific domain. The relative frequency of ETV6-RT resulted 2.6% in the whole case series and 4.6% among the families with known forms of inherited thrombocytopenia. The degree of thrombocytopenia and bleeding tendency of ETV6-RT patients were mild, but 4 subjects developed B-cell acute lymphoblastic leukemia during childhood, resulting in a significantly increased incidence compared to the general population. Clinical and laboratory findings did not identify any peculiar defects that can be used to suspect this disorder by routine diagnostic workup. However, at variance with most inherited thrombocytopenias, platelet size was not enlarged. In vitro studies revealed that patients megakaryocytes have defective maturation and impaired proplatelet formation. Moreover, ETV6-RT platelets have reduced ability to spread on fibrinogen. Since also the dominant thrombocytopenias due to mutations in RUNX1 and ANKRD26 are characterized by normal platelet size and predispose to hematological malignancies, we suggest that mutation screening of ETV6, RUNX1 and ANKRD26 should be performed in all the subjects with autosomal dominant thrombocytopenia and normal platelet size.

MYH9-related disease: a novel prognostic model to predict the clinical evolution of the disease based on genotype-phenotype correlations. - Pecci, Alessandro; Klersy, Catherine; Gresele, Paolo; Lee, Kieran J D; De Rocco, Daniela; Bozzi, Valeria; Russo, Giovanna; Heller, Paula G; Loffredo, Giuseppe; Ballmaier, Matthias; Fabris, Fabrizio; Beggiato, Eloise; et al. (Hum Mutat, 2014)
MYH9-related disease (MYH9-RD) is a rare autosomal-dominant disorder caused by mutations in the gene for nonmuscle myosin heavy chain IIA (NMMHC-IIA). MYH9-RD is characterized by a considerable variability in clinical evolution: patients present at birth with only thrombocytopenia, but some of them subsequently develop sensorineural deafness, cataract, and/or nephropathy often leading to end-stage renal disease (ESRD). We searched for genotype-phenotype correlations in the largest series of consecutive MYH9-RD patients collected so far (255 cases from 121 families). Association of genotypes with noncongenital features was assessed by a generalized linear regression model. The analysis defined disease evolution associated to seven different MYH9 genotypes that are responsible for 85% of MYH9-RD cases. Mutations hitting residue R702 demonstrated a complete penetrance for early-onset ESRD and deafness. The p.D1424H substitution associated with high risk of developing all the noncongenital manifestations of disease. Mutations hitting a distinct hydrophobic seam in the NMMHC-IIA head domain or substitutions at R1165 associated with high risk of deafness but low risk of nephropathy or cataract. Patients with p.E1841K, p.D1424N, and C-terminal deletions had low risk of noncongenital defects. These findings are essential to patients' clinical management and genetic counseling and are discussed in view of molecular pathogenesis of MYH9-RD.
Keywords: Adult; Age of Onset; Amino Acid Substitution; Cataract; Female; Genetic Association Studies; Genotype; Hearing Loss, Sensorineural; Humans; Italy; Linear Models; Male; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Phenotype; Risk Factors; Thrombocytopenia

Platelet diameters in inherited thrombocytopenias: analysis of 376 patients with all known disorders. - Noris, Patrizia; Biino, Ginevra; Pecci, Alessandro; Civaschi, Elisa; Savoia, Anna; Seri, Marco; Melazzini, Federica; Loffredo, Giuseppe; Russo, Giovanna; Bozzi, Valeria; Notarangelo, Lucia Dora; Gresele, Paolo; et al. (Blood, 2014)
Abnormalities of platelet size are one of the distinguishing features of inherited thrombocytopenias (ITs), and evaluation of blood films is recommended as an essential step for differential diagnosis of these disorders. Nevertheless, what we presently know about this subject is derived mainly from anecdotal evidence. To improve knowledge in this field, we evaluated platelet size on blood films obtained from 376 patients with all 19 forms of IT identified so far and found that these conditions differ not only in mean platelet diameter, but also in platelet diameter distribution width and the percentage of platelets with increased or reduced diameters. On the basis of these findings, we propose a new classification of ITs according to platelet size. It distinguishes forms with giant platelets, with large platelets, with normal or slightly increased platelet size, and with normal or slightly decreased platelet size. We also measured platelet diameters in 87 patients with immune thrombocytopenia and identified cutoff values for mean platelet diameter and the percentage of platelets with increased or reduced size that have good diagnostic accuracy in differentiating ITs with giant platelets and with normal or slightly decreased platelet size from immune thrombocytopenia and all other forms of IT.
Keywords: Adolescent; Adult; Blood Platelets; Case-Control Studies; Cell Size; Child; Child, Preschool; Diagnosis, Differential; Female; Hearing Loss, Sensorineural; Humans; Infant; Male; Middle Aged; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Purpura, Thrombocytopenic, Idiopathic; Thrombocytopenia; Young Adult

Alteration of liver enzymes is a feature of the MYH9-related disease syndrome. - Pecci, Alessandro; Biino, Ginevra; Fierro, Tiziana; Bozzi, Valeria; Mezzasoma, Annamaria; Noris, Patrizia; Ramenghi, Ugo; Loffredo, Giuseppe; Fabris, Fabrizio; Momi, Stefania; Magrini, Umberto; Pirastu, Mario; et al. (PLoS One, 2012)
BACKGROUND: MYH9-related disease (MYH9-RD) is a rare autosomal dominant genetic syndrome characterized by congenital thrombocytopenia associated with the risk of developing progressive nephropathy, sensorineural deafness, and presenile cataract. During the collection of a large case-series of patients with MYH9-RD we noticed several cases with unexplained elevation of liver enzymes. Our aim was to evaluate if the alteration of liver tests is a feature of the MYH9-RD and to define its clinical significance. METHODS AND FINDINGS: Data concerning liver tests, prospectively recorded in the Italian Registry for MYH9-RD, were collected and compared with those of three control populations: patients with autoimmune thrombocytopenia, patients with inherited thrombocytopenias other than MYH9-RD, and the participants to a large epidemiologic survey in an Italian geographic isolate. Thirty-eight of 75 evaluable MYH9-RD patients (50.7%) showed an elevation of ALT and/or AST, and 17 of 63 (27.0%) an increase of GGT. The increases ranged from 1.9 ± 0.7 to 2.7 ± 1.6 fold the upper normal limit. The prevalence of liver test alterations was significantly higher in MYH9-RD patients than in each of the control populations, with odds ratios ranging from 8.2 (95% CIs 2.2-44.8) to 24.7 (14.8-40.8). Clinical follow-up and more detailed liver studies of a subset of patients, including ultrasound liver scan, liver elastography and liver biopsy in one case, did not show any significant structural damage or evolution towards liver insufficiency. CONCLUSIONS: Elevation of liver enzymes is a frequent and previously unrecognized feature of the MYH9-RD syndrome; however, this defect does not appear to have poor prognostic value.
Keywords: Abnormalities, Multiple; Adolescent; Adult; Aged; Aged, 80 and over; Biopsy; Case-Control Studies; Child; Child, Preschool; Demography; Female; Follow-Up Studies; Humans; Immunohistochemistry; Infant; Liver; Liver Function Tests; Male; Middle Aged; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Odds Ratio; Syndrome; Young Adult

Clinical and genetic aspects of Bernard-Soulier syndrome: searching for genotype/phenotype correlations. - Savoia, Anna; Pastore, Annalisa; De Rocco, Daniela; Civaschi, Elisa; Di Stazio, Mariateresa; Bottega, Roberta; Melazzini, Federica; Bozzi, Valeria; Pecci, Alessandro; Magrin, Silvana; Balduini, Carlo L; Noris, Patrizia (Haematologica, 2011)
BACKGROUND: Bernard-Soulier syndrome is a severe bleeding disease due to a defect of GPIb/IX/V, a platelet complex that binds the von Willebrand factor. Due to the rarity of the disease, there are reports only on a few cases compromising any attempt to establish correlations between genotype and phenotype. In order to identify any associations, we describe the largest case series ever reported, which was evaluated systematically at the same center. DESIGN AND METHODS: Thirteen patients with the disease and seven obligate carriers were enrolled. We collected clinical aspects and determined platelet features, including number and size, expression of membrane glycoproteins, and ristocetin induced platelet aggregation. Mutations were identified by direct sequencing of the GP1BA, GP1BB, and GP9 genes and their effect was shown by molecular modeling analyses. RESULTS: Patients all had a moderate thrombocytopenia with giant platelets and a bleeding tendency whose severity varied among individuals. Consistent with expression levels of GPIbα always lower than 10% of control values, platelet aggregation was absent or severely reduced. Homozygous mutations were identified in the GP1BA, GP1BB and GP9 genes; six were novel alterations expected to destabilize the conformation of the respective protein. Except for obligate carriers of a GP9 mutation with a reduced GPIb/IX/V expression and defective aggregation, all the other carriers had no obvious anomalies. CONCLUSIONS: Regardless of mutations identified, the patients' bleeding diathesis did not correlate with thrombocytopenia, which was always moderate, and platelet GPIbα expression, which was always severely impaired. Obligate carriers had features similar to controls though their GPIb/IX/V expression showed discrepancies. Aware of the limitations of our cohort, we cannot define any correlations. However, further investigations should be encouraged to better understand the causes of this rare and underestimated disease.
Keywords: Adolescent; Adult; Amino Acid Sequence; Bernard-Soulier Syndrome; Blood Platelets; Cell Shape; Child; Child, Preschool; Female; Genetic Association Studies; Genetic Markers; Hemorrhage; Homozygote; Humans; Italy; Male; Membrane Glycoproteins; Middle Aged; Molecular Sequence Data; Platelet Aggregation; Platelet Count; Platelet Glycoprotein GPIb-IX Complex; Point Mutation; Polymerase Chain Reaction; Ristocetin; Thrombocytopenia; von Willebrand Factor; Young Adult

Mutations in the 5' UTR of ANKRD26, the ankirin repeat domain 26 gene, cause an autosomal-dominant form of inherited thrombocytopenia, THC2. - Pippucci, Tommaso; Savoia, Anna; Perrotta, Silverio; Pujol-Moix, Núria; Noris, Patrizia; Castegnaro, Giovanni; Pecci, Alessandro; Gnan, Chiara; Punzo, Francesca; Marconi, Caterina; Gherardi, Samuele; Loffredo, Giuseppe; et al. (Am J Hum Genet, 2011)
THC2, an autosomal-dominant thrombocytopenia described so far in only two families, has been ascribed to mutations in MASTL or ACBD5. Here, we show that ANKRD26, another gene within the THC2 locus, and neither MASTL nor ACBD5, is mutated in eight unrelated families. ANKRD26 was also found to be mutated in the family previously reported to have an ACBD5 mutation. We identified six different ANKRD26 mutations, which were clustered in a highly conserved 19 bp sequence located in the 5' untranslated region. Mutations were not detected in 500 controls and are absent from the 1000 Genomes database. Available data from an animal model and Dr. Watson's genome give evidence against haploinsufficiency as the pathogenetic mechanism for ANKRD26-mediated thrombocytopenia. The luciferase reporter assay suggests that these 5' UTR mutations might enhance ANKRD26 expression. ANKRD26 is the ancestor of a family of primate-specific genes termed POTE, which have been recently identified as a family of proapoptotic proteins. Dysregulation of apoptosis might therefore be the pathogenetic mechanism, as demonstrated for another thrombocytopenia, THC4. Further investigation is needed to provide evidence supporting this hypothesis.
Keywords: Ankyrin Repeat; Base Sequence; Chromosome Breakage; Chromosome Disorders; Conserved Sequence; Female; Genes, Dominant; Genetic Loci; Haploinsufficiency; Humans; Male; Molecular Sequence Data; Mutation; Pedigree; Thrombocytopenia

Eltrombopag for the treatment of the inherited thrombocytopenia deriving from MYH9 mutations. - Pecci, Alessandro; Gresele, Paolo; Klersy, Catherine; Savoia, Anna; Noris, Patrizia; Fierro, Tiziana; Bozzi, Valeria; Mezzasoma, Anna Maria; Melazzini, Federica; Balduini, Carlo L (Blood, 2010)
Platelet transfusion is currently the primary medical treatment for reducing thrombocytopenia in patients with inherited thrombocytopenias. To evaluate whether stimulating megakaryopoiesis could increase platelet count in these conditions, we treated patients with a severe thrombocytopenia induced by MYH9 mutations (MYH9-related disease) with a nonpeptide thrombopoietin receptor agonist, eltrombopag. Twelve adult patients with MYH9-RD and platelet counts of less than 50 × 10(9)/L received 50 mg of eltrombopag orally per day for 3 weeks. Patients who achieved a platelet count higher than 150 × 10(9)/L stopped therapy, those with 100 to 150 platelets × 10(9)/L continued treatment at the same eltrombopag dose for 3 additional weeks, while those with less than 100 platelets × 10(9)/L increased the eltrombopag dose to 75 mg for 3 weeks. Major responses (platelet count of at least 100 × 10(9)/L or 3 times the baseline value) were obtained in 8 patients, minor responses (platelet counts at least twice the baseline value) in 3. One patient did not respond. Bleeding tendency disappeared in 8 of 10 patients with bleeding symptoms at baseline. Mild adverse events were reported in 2 patients. The availability of thrombopoietin mimetics opened new prospects in the treatment of inherited thrombocytopenias. This study is registered at www.clinicaltrials.gov as NCT01133860 (European Union Drug Regulating Authorities Clinical Trials number 2008-001903-42).
Keywords: Administration, Oral; Adolescent; Adult; Benzoates; Dose-Response Relationship, Drug; Female; Genetic Predisposition to Disease; Humans; Hydrazines; Male; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Platelet Aggregation; Platelet Count; Pyrazoles; Receptors, Thrombopoietin; Survival Rate; Thrombocytopenia; Treatment Outcome; Young Adult